Infections and infertility due to tubal factor - L Chamani Tabriz (JRI, 2000)
Tubal factors are most important causes of infertility and are attributed to several etiologies. It seems that infections cause 10% to 70% of tubal factors and are strongly depended on patients age, numbers of infections and geogarphical and regional epidemiology. All types of tubal inflamations can impair fertility such as: acute salpingitis, tubo–ovarian abscess formation, asympothomatic involvement, and chronic salpingitis The most important organisms which parcipitate in acute salpigitis are caused by: Neiserria gonorrhea, Chlamydia trachonatis, anaerobe and gram negative organisms. The wold Health Organization (WHO) and The Centre of Disease Control and prevention (CDC) have special attentions on rapid diagnosis and treatment of the disease for preventing further infertility and even fatal results. They suggest different empirical therapy protocols suspecting the most common organisms. Chlamydia trachomatis is the most common organism causing chronic Salpingitis. Mycobacterium tuberculosis and Coccidioies immitis are the next common organisms. With attention to their chronic coarse, epidemiology and patient’s signs physician should choose differrent approaches.
Keywords: Infections, Infertility, Tubal Factor